Comparative Analysis of Direct Inhalation vs. Diffuser Delivery Methods for Lavender Aromatherapy on Pain Intensity in Primigravida During Active Labor Phase - Yeni Fitrianingsih, Yeni fitria (Midwifery and Nursing Research, 2024)
Background: Pain is an uncomfortable feeling that everyone has experienced, whether mild or acute. The intensity of labor pain in primigravidas is often more severe than labor pain in multiparas. Aromatherapy is a non-pharmacological method for treating, reducing symptoms, preventing and reducing anxiety. Using lavender aromatherapy can increase relaxation and reduce pain. Providing aromatherapy through inhalation is the most popular method of administration. However, there has been no research that proves a more effective method of administration in reducing labor pain between direct inhalation aromatherapy and using a diffuser. Aromatherapy has not been widely developed in PMB Cirebon city. The aim was to determine the difference between giving lavender aromatherapy by direct inhalation and diffuser on pain intensity in active phase I primigravidas in BPM Cirebon Regency. Methods: Quasi Experiment research with a two group pre-test and post-test design. The independent variable in this research is the administration of lavender aromatherapy by direct inhalation using a diffuser. The dependent variable in this research is the intensity of labor pain. Population of all primigravida mothers. Non Random Sampling technique with Accidental Sampling with inclusion and exclusion criteria. The inclusion criteria in this study were primigravida, Term (37-42 weeks), Inpartu, Phase I active phase, Age 20-35 years, Patient willing to be a research respondent The study exclusion criteria were pathological labor, allergies to aromatherapy odors, olfactory disorders (flu). The number of samples was 30 people. 15 people were given aromatherapy by inhaling directly and 15 people by using a diffuser. Univariate and bivariate data analysis. The bivariate test uses the Wilcoxon Signed Rank and Mann Whitney tests. Results: The results of the Wilcoxon test for the direct inhalation group had a p-value of 0.157. The results of the diffuser group have a p value of 0.001. Mann Whitney test results p value of 0.001. So giving lavender aromatherapy using a diffuser is more effective in reducing labor pain. Conclusion: There are differences in the intensity of labor pain when giving direct inhalation of lavender aromatherapy and using a diffuser. Diffuser aromatherapy is more effective in reducing labor pain